Answer:
• The function f is increasing to the left of -4 (-∞ , -4]
• The function f is decreasing to the right of -4 [-4 , +∞)
Step-by-step explanation:
f(x) = -(x+6)(x+2)
= -(x² + 2x + 6x + 12)
= -(x² + 8x + 12)
= -x² - 8x - 12
The leading coefficient is -1 (the coefficient of the highest term -x² of the trinomial)
Then
The parabola opens downward.
………………………………………
[tex]-\frac{b}{2a} =-\frac{-8}{2\times \left( -1\right) } =-4[/tex]
Then
The function f is increasing to the left of -4 (-∞ , -4]
The function f is decreasing to the right of -4 [-4 , +∞)